1983
DOI: 10.1111/j.2044-8279.1983.tb02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Expectations and Perceptions of Polynesian and Pakeha Pupils and the Relationship to Classroom Behaviour and School Achievement

Abstract: SUMMARY.A study of 90 nine-year-olds in five ethnically mixed New Zealand classrooms was undertaken to investigate teachers' perceptions of Polynesian and Pakeha pupils and the relationship of these perceptions to expectations for general ability. Results showed that the Polynesian minority group pupils were perceived less favourably than the Pakeha majority on dimensions reflecting parent-home factors and academic work skills. In line with this, teachers held lower expectations for the ability of Polynesian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
2
7
0
1
Order By: Relevance
“…Stoddart found significant differences in teacher perceptions (with those for Maori always being significantly lower) for knowledge of strategies needed to perform socially appropriate behaviours, for the ability to perform socially acceptable behaviours, and for awareness of the effects that the child's actions have on the social environment. These results align somewhat with the findings of St. George (1983) who found that teachers had less favourable views of the academic work skills (e.g.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Stoddart found significant differences in teacher perceptions (with those for Maori always being significantly lower) for knowledge of strategies needed to perform socially appropriate behaviours, for the ability to perform socially acceptable behaviours, and for awareness of the effects that the child's actions have on the social environment. These results align somewhat with the findings of St. George (1983) who found that teachers had less favourable views of the academic work skills (e.g.…”
supporting
confidence: 92%
“…Maori students, on the other hand, are believed to come from families where education is not valued and where parents are not encouraging of teachers' efforts. St. George (1983) made similar comments in relation to her finding that teachers judged the Polynesian students in her study (most of whom were Maori) to come from less supportive home backgrounds than the New Zealand European students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further implication of teachers' expectations is that when teachers have high expectations for some students and low for others this may lead to a halo effect in which teachers also perceive there to be differences in student characteristics. St George (1983) investigated the relationship between teacher perceptions of student characteristics and expectations for student performance. The results revealed that Maori students in New Zealand were perceived more negatively by their teachers than were New Zealand European students (St George, 1983) and their teachers also held lower expectations for their achievement.…”
Section: Teacher Behaviours With High and Low Expectation Studentsmentioning
confidence: 99%
“…Citons, entre autres, les études de Clifton (1981) sur des élèves ontariens, de Matthews (1982) sur des élèves anglais du secondaire et de St-George (1983) sur des élèves du primaire de NouvelleZélande.…”
unclassified